Early Switch From Tacrolimus to Everolimus After Liver Transplantation: Outcomes at 2 Years. Issue 12 (19th November 2019) - Saliba, Faouzi; Duvoux, Christophe; Dharancy, Sébastien; Dumortier, Jérôme; Calmus, Yvon; Gugenheim, Jean; Kamar, Nassim; Salamé, Ephrem; Neau‐Cransac, Martine; Vanlemmens, Claire; Durand, François; Pageaux, Georges; et al.
Abstract : The observational CERTITUDE study follows liver transplant patients who completed the SIMCER trial. SIMCER randomized patients at month 1 after transplant to everolimus (EVR) with stepwise tacrolimus (TAC) withdrawal or to standard TAC, both with basiliximab induction and mycophenolic acid ± steroids. After completing SIMCER at 6 months after transplant, 65 EVR‐treated patients and 78 TAC‐treated patients entered CERTITUDE. At month 24 after transplant, 34/65 (52.3%) EVR‐treated patients remained calcineurin inhibitor (CNI) free. Mean estimated glomerular filtration rate (eGFR) was significantly higher with EVR versus TAC during months 3‐12. At month 24, eGFR values were 83.6 versus 75.3 mL/minute/1.73 m 2, respectively ( P  = 0.90) and adjusted mean change in eGFR from randomization was −8.0 versus −13.5 mL/minute/1.73 m 2 ( P  = 0.15). At month 24, 45.9%, 31.1%, and 23.0% of EVR‐treated patients had chronic kidney disease stages 1, 2, and 3, respectively, versus 25.7%, 45.7%, and 28.6% of TAC‐treated patients ( P  = 0.05). Treated biopsy‐proven acute rejection affected 4 EVR‐treated patients and 2 TAC patients during months 6‐24. Adverse events led to study discontinuation in 15.4% and 7.7% of EVR‐treated and TAC‐treated patients, respectively. Grade 3 or 4 hematological events were rare in both groups. A CNI‐free EVR‐based maintenance regimen appears feasible in approximately half of liver transplant patients. It preserves renal function effectively with good efficacy without compromising safety or hematological tolerance.